Macromolecular rate theory (MMRT) provides a thermodynamics rationale to underpin the convergent temperature response in plant leaf respiration. (14th November 2017) - Liang, Liyin L.; Arcus, Vickery L.; Heskel, Mary A.; O'Sullivan, Odhran S.; Weerasinghe, Lasantha K.; Creek, Danielle; Egerton, John J. G.; Tjoelker, Mark G.; Atkin, Owen K.; Schipper, Louis A.
Abstract: Temperature is a crucial factor in determining the rates of ecosystem processes, for example, leaf respiration ( R ) – the flux of plant respired CO2 from leaves to the atmosphere. Generally, R increases exponentially with temperature and formulations such as the Arrhenius equation are widely used in earth system models. However, experimental observations have shown a consequential and consistent departure from an exponential increase in R . What are the principles that underlie these observed patterns? Here, we demonstrate that macromolecular rate theory (MMRT), based on transition state theory (TST) for enzyme‐catalyzed kinetics, provides a thermodynamic explanation for the observed departure and the convergent temperature response of R using a global database. Three meaningful parameters emerge from MMRT analysis: the temperature at which the rate of respiration would theoretically reach a maximum (the optimum temperature, T opt ), the temperature at which the respiration rate is most sensitive to changes in temperature (the inflection temperature, T inf ) and the overall curvature of the log(rate) versus temperature plot (the change in heat capacity for the system, Δ C P ‡ ). On average, the highest potential enzyme‐catalyzed rates of respiratory enzymes for R are predicted to occur at 67.0 ± 1.2°C and the maximum temperature sensitivity at 41.4 ± 0.7°C from MMRT. The average curvature (average negative Δ C P ‡ ) was −1.2 ± 0.1 kJ mol −1 K −1 . Interestingly, T opt, T inf and Δ C P ‡ appear insignificantly different across biomes and plant functional types, suggesting that thermal response of respiratory enzymes in leaves could be conserved. The derived parameters from MMRT can serve as thermal traits for plant leaves that represent the collective temperature response of metabolic respiratory enzymes and could be useful to understand regulations of R under a warmer climate. MMRT extends the classic TST to enzyme‐catalyzed reactions and provides an accurate and mechanistic model for the short‐term temperature response of R around the globe. Abstract : Macromolecular rate theory (MMRT) predicts the temperature response of leaf respiration consistently better than the Arrhenius model around the globe (673 plant leaves tested). MMRT provides a thermodynamic explanation for the observed departure from an exponential increase predicted by Arrhenius model and the convergent temperature response of leaf respiration. MMRT extends the classic transition state theory to explore the thermodynamic properties of respiratory enzymes and the derived parameters from MMRT can serve as thermal traits for plant leaves.